Effects of diamond grain size on magnetic properties of the cobalt phase in PCD compacts - Ngwekhulu, Tsholofelo Themba (My University, 2018)
This research was aimed at a broad description of polycrystalline diamond (PCD) compacts sintering and effects of metal sintering aid infiltration into PCD. It concerned an investigation into the influence of diamond grain size on metal phase magnetic properties in PCD. In particular, a relationship between magnetic parameters and PCD microstructure has been investigated. The polycrystalline diamond (PCD) table utilized for investigation comprised diamond grains, which were non-magnetic, a metal phase (cobalt), which was the only ferromagnetic part in the material and WC which was non-magnetic and which moved into PCD during cobalt infiltration. Sintered PCD compacts having mean grain sizes of 4.5 μm, 13 μm and 25.3 μm were assessed respectively. The PCD tables without the substrate material were prepared by Electron Discharge Machining (EDM) and characterized by means of Scanning Electron Microscopy (SEM), Image Analysis (IA) and Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES). Magnetic saturation and coercive field strengths were resolved using KOERZIMAT 1.097 and KOERZIMAT CS 1.096 measuring systems. Strong correlation was seen between the metal phase content and magnetic saturation and also in cobalt mean-free path and coercivity. The analysis demonstrated that the shape and size of the specimen has no impact on the magnetic saturation parameter, and further investigation showed that increasing the grain size of the non-magnetic diamond phase decreases the number of magnetic domains of a metallic cobalt phase, but increases the coercive force. In WC-Co coercivity is high when WC grains are fine. The research has demonstrated that the diamond starting particle size has substantial impact on the metallic phase microstructure and magnetic properties in general. Additionally, the results demonstrated that PCD made with fine diamond particles has greater PCD density as a function of metal content in comparison to coarser diamond particles showing a higher volume fraction of metallic cobalt due to the fact that the former includes much smaller average number of contact points and thus much higher contact stresses, and furthermore has greater surface to volume ratio as well as a lower packing density. Characterisation results have demonstrated a strong correlation and showed that changing the grain size of the non-metallic phase has significant impact on the subsequent microstructure and material properties of the PCD.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science (Physics) October 2018
Keywords: Phase rule and equilibrium; Metallurgical analysis